Management of autism spectrum disorder through Ayurveda - A case report - Masooda; Vijay Kumar Pathak; Arun Kumar Mahapatra; Rajagopala Shrikrishna (Wolters Kluwer Medknow Publications, 2023)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders marked by impairment in varying degrees of social communication and interaction, repetitive behaviors, and restricted interests. Based on clinical characteristics, ASD can be correlated with Unmada mentioned in Ayurveda classics. In clinical practice, there is a paucity of standard treatment protocols and effective care for the prevention of ASD. The present case report discusses a 5-year-old male patient who presented with poor eye contact, no communication, no social skills, poor speech, repetitive play activity, hyperactivity, constipation, and sleep disturbances reported at Kaumarabhritya outpatient department. Diagnosis of ASD was established using the Indian Scale for Assessment of Autism (ISAA) test manual. Abhyanga with Ksheerbala Taila and Nasya with Saraswata Ghrita along with other internal medications i.e., Saraswata Ghrita, Ashwagandharista, Guduchi Churna, Madhuyashthi Churna, and Vacha Churna were given. Remarkable improvement was noted in overall ISAA scores as well as clinical improvement noted in poor eye contact, hyperactivity, and peer relationship. "Child Sleep Habit Questionnaire (CSHQ)" was used to assess the child's sleep pattern and improvement was noted. The stress level of the parent also decreased which was assessed using the "Autism Parenting Stress Index." No adverse effects were reported during the treatment period and follow-up.